APLIKASI KEMOMETRIK UNTUK MENENTUKAN ASAM LEMAK BEBAS MINYAK GORENG SECARA NIR SPEKTROSKOPI - Leny Irawati; Basim Thariq; Maman Suherman; Aisyah Permata Rosadi (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Free fatty acids (FFA) is a parameters to determine the quality of cooking oil. FFA in cooking oil can be determined by acidy-alcalimetry titration, GC or HPLC methods. These methods use a lot of consumables and require a long time. The aims of this research is to examine the NIR Spectroscopy method as an alternative for determining the FFA of cooking oil. This method is non-destructive, less preparation, does not use consumables and can be done in a short time. The research began by collecting FFA data from thirty samples and NIR spectrum data for each sample. Through chemometric approaches, data obtained from the NIR spectrum and analysis conventional FFA were analyzed multivariately using software NIRCal Chemometric from Buchi . The calibration curve obtained can be used to prediction the FFA of a cooking oil by plotting the results of the NIR Infrared spectrum of the sample against the calibration curve . The results show that FFA values for several cooking oil sampel that use the NIR Spectroscopy method are relatively the same as conventional method so that the NIR Spectroscopy can be used as an alternative method to determine FFA in cooking oil.